Gender, race, and nation : a global perspective - Dhruvarajan, Vanaja; Vickers, Jill, 1942- (University of Toronto Press, 2002)
The terms 'Woman' and 'Women' have been the organizing concepts for feminist politics and scholarship on women in western countries for several centuries. 'Women', it was assumed, shared characteristics based on biology and experiences of subordination; other aspects of their lives, such as language, national or ethnic identity, 'race', or sexual orientation were considered secondary to the identity of woman-ness. In this work, Dhruvarajan and Vickers call into question feminism's presumed universality of gender analysis, and bring to the foreground the voices of marginalized women in Western society, and of women outside of the western world. Gender, Race, and Nation discusses opening scholarship to the experiences of women in all of their diversity, making links between the differences in local contexts and global contexts, and relating to other women with the understanding of each woman's relative position in terms of power and privilege to facilitate coalition building and develop strategies to address issues of common concern to usher in a just and caring world for all. This change in perspective presented by Dhruvarajan and Vickers represents a paradigm shift in the study of women and women's issues, and forges a new approach to women's studies/scholarship on women, women' s movements, and global social transformation.